Living in the American style: an analysis of House Beautiful magazine, 1935-1955 - Smith, Elizabeth A. (Kansas State University, 2010)
The years of World War II mark a time of significant sociological and cultural change. In the United States, new technologies were introduced, and family structure and family economics changed. These changes were reflected in the popular media, including housing design publications. This thesis examines the design of the American house from 1935 to 1955 as presented in House Beautiful, originally The House Beautiful and first published in 1896, and how it changed during this twenty-year period. Seven themes were used to organize and describe change during this period. These themes are: 1) family structure and economics, 2) technology, 3) construction, 4) automobile, 5) site and spatial relationships, 6) status, and 7) privacy. Changes in presentation of the house in House Beautiful are shown by comparing and contrasting feature house articles across the twenty-year study period. The focus audience of House Beautiful magazine was what the publishers of House Beautiful characterized as the average American, while in fact the designs were not for the masses. Rather, the magazine catered to the ideal image of the average American. Trends discussed in relation to changes in house design include the following: family stability and security, privacy, home-ownership, transportation, suburban development, the process of Americanization, quality of life, and household efficiency.
Keywords: House Beautiful magazine; Trends; Residential design; Architecture (0729); History, United States (0337)